Waste Analysis In CPO Production Using Lean Six Sigma - Nababan, Yohanes; Rochmoeljati, Rochmoeljati (Journal La Multiapp, 2025)
PT XYZ is a manufacturing company engaged in the production of Crude Palm Oil (CPO). In its production process, a significant amount of waste due to product defects is still found. This can be seen from the production parameters recorded from January to June 2024. Based on 137 samples taken over six months, 132 samples did not meet the company's established standards across four parameters. This study aims to determine the types of waste occurring in the CPO production process, assess the sigma level, provide waste reduction recommendations, and minimize non-value-added activities. The study uses the Lean Six Sigma method. It begins by identifying waste in the CPO production process, with the most dominant forms being defects, overproduction, and waiting. The sigma level of the CPO production process at PT XYZ was found to be 2.20, with a DPMO (Defects Per Million Opportunities) of 240,277.8, which falls into the "good" category based on the average performance of the palm oil industry in Indonesia. Further analysis was conducted to identify the root causes of defects using a fishbone diagram. Improvement proposals were developed using the Failure Mode and Effect Analysis (FMEA) tool. With the design of Process Activity Mapping (PAM) and Big Picture Mapping, the lead time was successfully reduced from 807.22 minutes to 728.88 minutes.